Virtual Money Exchange (Cryptocurrency) with Real Money (Rupiah) based on Sharia Economic Law Perspective - Masithoh Masithoh; Ahmad Imam Hambali (Ridwan Institute, 2022)
The purpose of this research is to analyze the exchange of virtual cryptocurrency money with real rupiah money from the perspective of sharia economic law. Currently there is a lot of money in virtual form, one of which is bitcoin. The emergence of this type of virtual money is proof of one of the latest technological advances. Bitcoin has been widely used by several countries and even makes it a transaction tool. Cryptocurrency is becoming a booming trend as a new investment opportunity. Not even a few believe that crypto becomes an attraction because it is considered to have different characteristics in solving expenses without using a third party. Some of the provisions in the exchange contract between the same and different currencies, namely exchanging money with similar types such as rupiah with Rupiah and must be done in cash, if different currencies such as Rupiah and Dollar must also be in cash, if the exchange occurs between money and commodities, the most important thing is agreement between the seller and the buyer. Cryptocurrency (Bitcoin) is legal to use for people who accept and acknowledge it, but MUI and OJK do not allow it as a commodity and similarly BI does not allow it as a legal transaction tool to be used in Indonesia because it is considered not to meet the requirements as a currency like Rupiah. and in the perspective of sharia economic law that cryptocurrency (Bitcoin) is an object or object that is not allowed (haram).